Olfactory functioning in early multiple sclerosis: Sniffin’ Sticks Test study - Batur Caglayan H; Irkec C; Nazliel B; Akyol Gurses A; Capraz I (Neuropsychiatric Disease and Treatment, 2016)
Hale Z Batur Caglayan,1 Ceyla Irkec,1 Bijen Nazliel,1 Aslı Akyol Gurses,2 Irem Capraz11Department of Neurology, Faculty of Medicine, Gazi University, Ankara, 2Department of Neurology, Meram Faculty of Medicine, Necmettin Erbakan University, Konya, Turkey Introduction: Previous studies have shown that olfactory functioning is affected by multiple sclerosis (MS). This study assessed the level of the olfactory impairment in early MS by using the Sniffin’ Sticks Test.Methods: This study included 30 patients with MS and 30 healthy controls. We collected demographic and clinical data from participants and administered the Sniffin’ Sticks Test.Results: We found no differences between the MS and control groups in odor discrimination, odor identification, and threshold discrimination identification scores, but odor threshold (OT) scores were higher in the control group than in the MS group (P=0.49). In addition, we did not find any correlation between MS patients’ olfactory test scores and their scores on the Mini–Mental State Examination (MMSE), Expanded Disability Status Scale (EDSS), disease duration, history of optic neuritis, or being on immunomodulatory therapy. Conclusion: In recent studies, odor threshold impairment seemed to be the most striking finding in patients with MS. Although the present study found a mild alteration in odor threshold, olfactory dysfunction appears to be a consequence of neurodegeneration in the higher order olfactory brain regions, which is thought to be a time-dependent process. Keywords: demyelinating diseases, multiple sclerosis, odors, olfaction, olfaction disorders, smell